Awareness and utilisation of quitline among current tobacco users in a district in southern india - Mullapudi, Somya; Kamath, Veena G; Kulkarni, Muralidhar M; Kamath, Asha; Bhagawath, Rohith; Nayak, Radhika (Indian Journal of Community Health, 2021)
Background: Tobacco use not only increases mortality, but also causes enormous burden to the Nation’s health and economy. The WHO -Framework Convention on Tobacco Control implemented “MPOWER”, comprising of an important entity of ‘offering help to tobacco users’ to quit. Quitline provides evidence-based treatment services to tobacco users and advertising those services has the potential to increase their utilisation. Objectives: Our objective was to assess the awareness and utilisation of the newly introduced quitline on tobacco packs among tobacco users. Materials and Methods: After obtaining Ethics Committee approval, this cross-sectional study was conducted from March-June 2019 in a purposive sample of tobacco users aged 18 years and above at the point of sale with prior informed consent. The questionnaire included questions on the users’ knowledge and utilisation of the quitline. Results: Most of the tobacco users (84.6 %) had not observed the quitline on tobacco pack. Amongst those who observed the quitline, 65.5% were smokers, while the smokeless tobacco users who comprised half of the study population were unaware of the quitline. More than 97% of illiterates were unaware of the quitline. Only three tobacco users who were aware of quitline had tried using it. Conclusion: Most of the tobacco users had basic education but were not aware of the quitline on the tobacco packs and only a very few of them used the services, highlighting the need to increase its awareness for effective tobacco control.